Super, social, medical: Person-first and identity-first representations of disabled people in Australian newspapers, 2000–2019. (July 2023) - Potts, Amanda; Bednarek, Monika A; Watharow, Annmaree
This paper provides an interdisciplinary, corpus-based study of naming practices for disabled people in a collection of Australian newspaper articles spanning 20 years. We analyse head nouns, modifiers, and coordinating structures for both person-first and identity-first language, drawing on social actor analysis as well as previously-identified models of media representation. Overall, we find similar usage of both naming practices with respect to the types of social actors that occur, the categorisations of disabilities that are referenced, and the associations that are established, with only minor differences. Additionally, both naming practices are strongly associated with the medical and social pathology models of media representation, which emphasise disadvantage, with almost a total absence of 'progressive' models, which represent people as multifaceted agents. We conclude by emphasising the need for the news media to incorporate the voices and preferences of disabled people themselves.